16S rDNA barcoding technique for molecular identification of processed sea cucumbers from selected Malaysian markets - Kamarudin, Kamarul Rahim; Mohamed Rehan, Maryam; Mohd Noor, Hanina; Ramly, Nur Zazarina; Mohamed Rehan, Aisyah (2015)
Sea cucumber (Phylum Echinodermata: Class Holothuroidea) is renowned in Malaysia as a resource of food and medicine. In food industry, wide-ranging processing, including gutting, boiling, roasting, and subsequent preservation procedures for long storage are frequently needed prior to marketing and consumption of sea cucumbers. In fact, the processes cause deformation of original body shape that leads to difficulties in clear species identification and confirmation of marketed sea cucumbers. Besides, sea cucumber products in Malaysian markets are often intentionally unlabelled or mislabelled. Economic fraud, health hazards, and illegal trade of protected species are potential major consequences of the species substitution. Therefore, this study was conducted to determine species identities of processed sea cucumbers from selected Malaysian markets, i.e. Kuantan, Pahang (East Coast region of Peninsular Malaysia); Langkawi Island, Kedah (the Northern region); Kudat, Sabah (near the northernmost point of Borneo, East Malaysia) and Kota Kinabalu, Sabah (in the northwestern Borneo) in the forms of fresh (nine specimens) and dried (16 specimens) products. Five reference samples were included in the analyses consisting of fresh samples that were morphologically identified as Stichopus horrens (gamat species–specimens) and Holothuria (Mertensiothuria) leucospilota (timun laut species– three specimens) from Pangkor Island, Perak. No species details were tagged to most of the sea cucumber-based food products. Phylogenetic analyses of 30 partial sequences of non-protein-coding 16S mitochondrial ribosomal RNA (rRNA) gene using five main methods, i.e. Neighbour-Joining (NJ), Maximum Likelihood (ML), Minimum Evolution (ME), Unweighted Pair Group Method with Arithmetic Mean (UPGMA), and Maximum Parsimony (MP) showed the presence of two main families of sea cucumbers: Stichopodidae (gamat family) and Holothuriidae (timun laut family), and hence the Basic Local Alignment Search Tool (BLAST) results were supported. This study recorded seven sea cucumber species in total. Specimens of S. horrens, Stichopus herrmanni and Thelenota anax were the three gamat species that clustered under family Stichopodidae. Meanwhile, specimens of H. leucospilota, Holothuria (Halodeima) edulis, Holothuria (Metriatyla) scabra and H. scabra var. versicolor were the four timun laut species that clustered under family Holothuriidae.